Physical and biogeochemical drivers of solute mobilization and flux through the critical zone after wildfire - Sánchez, Rodrigo Andrés; Meixner, Thomas; Roy, Tirthankar; Ferré, Paul Ty; Whitaker, Martha; Chorover, Jon (Frontiers in Water, 2023)
A nine-year time series of nutrient cation and anion concentration and efflux from three forested catchments in the Jemez River Basin Critical Zone Observatory (JRB-CZO) in northern New Mexico was used to quantify the pulse of chemical denudation resulting from varying levels stand-replacing wildfire intensity in May-June of 2013. The three years of pre-fire and six years of postfire data were also probed to shed light on the mechanisms underlying the pulsed release and the subsequent recovery. The initial large solute pulse released to the streams—K+, Ca2+, Mg2+, SO42-, Cl-, DIC, DOC, and TDN—was caused by dissolution of hillslope ash deposits during the first monsoon storms post-fire. Debris flow following the wildfire likely redistributed much of the ash-containing sediments along streams and valley bottoms. Sustained elevated solute concentrations observed in the surface waters throughout the post-fire period relative to pre-fire baselines is consistent with these soluble materials being periodically flushed from the soils during wet seasons, i.e., snowmelt and summer monsoons. As microbial mediated reactions and biotic uptake—due to plant regrowth—recover after fire, nutrient ion export (e.g., NO3-, Cl- and SO42-) steadily decreased towards the end of the post fire period, but remained above pre-fire levels, particularly for NO3- and SO42-. Surface water concentrations of polyvalent cations (e.g., Al and Fe) decreased significantly after the fire. Our observations suggest that changes in organic matter composition after fire (e.g., increased HIX) and the presence of pyrogenic carbon may not favor organo-metal complexation and transport. Finally, differences in burn severity among the three watersheds presented in this study, provide insights of the relative impact of solute exports and resilience. The catchments that experienced high burn severity exhibited greater solute fluxes than the less severely burn. Moreover, despite these differences, towards the end of the post-fire period these surface waters presented low and similar solute effluxes, indicating system recovery. Nonetheless, magnitudes and rebounds were solute and process specific. The results of this study highlight the importance of surface and near surface physical and biogeochemical processes on the long-lasting geochemical denudation of forested catchments following wildfires of varying intensities.